ABCG2, SCN1A and CYP3A5 genes polymorphism and drug-resistant epilepsy in children: A case-control study. (April 2022) - Mousavi, Seyedeh Farnaz; Hasanpour, Kazem; Nazarzadeh, Milad; Adli, Abolfazl; Bazghandi, Malihe Sadat; Asadi, Alireza; Rad, Abolfazl; Gholami, Omid
Highlights: Pharmacogenetic pathways are one of the important elements that can help clinicians determine medication response and provide more efficient drug therapy, especially in cases of drug resistance. In this case-control study, we assessed the association between candidate SNPs in three genes ( CYP3A5, SCN1A, ABCG2) hypothesized to be associated with drug resistant epilepsy pathophysiology. We found a higher chance of drug resistant epilepsy associated with SNP rs2231137 (genotype C versus T) in ABCG2 gene. This finding may have important implications for understanding the role of ABCG2 gene polymorphism in children with drug resistant epilepsy. Abstract: Purpose: Drug Resistant -Epilepsy is still a major challenge in pharmacotherapy of epilepsy. Pharmacogenetic pathways are one of the most important elements that can help clinicians determine medication response and provide more efficient drug therapy, especially in cases of drug resistance. Genetic alterations in drug target and transporter proteins, in part, could explain the development of drug-resistant epilepsy. We sought to assess the association of CYP3A5 (rs776746), SCN1A (rs2298771) and ABCG2 (rs2231137) candidate polymorphisms with drug-resistant epilepsy among Iranian children with epilepsy. Methods: In a hospital-based case-control study, 93 participants, including 45 men and 48 women aged 1.5 to 14 years old were recruited. Genotyping of CYP3A5 (rs776746), SCN1A (rs2298771) and ABCG2 (rs2231137) polymorphisms using the high-resolution melting (HRM) method were measured in 46 children with drug-resistant epilepsy and 47 healthy control subjects. The binary logistic regression model was used to estimate the odds ratio (OR) for each polymorphism per effect allele increase. Results: The mean (standard deviation [SD]) age of the drug-resistant patients was 10.7 (9.0) years versus 7.3 (3.6) in the control group. In the case group, most of the patients with epilepsy were diagnosed with generalized seizure (about 87%) and negative epileptic history status (63%). Furthermore, idiopathic epilepsy was dominant in the case group (69%). There was a clinically meaningful increase in the chance of drug-resistant epilepsy in participants with candidate polymorphism in ABCG2 gene (per allele T increase, adjusted odds ratio [OR] 2.41, confidence interval [CI] 0.99 to 5.87, P=0.05). No significant association was found between CYP3A5 (per allele C increase, OR 0.92, CI 0.33 to 2.60, P= 0.88) and SCN1A (per allele *1 increase, OR 0.65, 95% CI 0.34 to 1.23, P= 0.19) with drug-resistant epilepsy. Conclusion: We found evidence for the relationship between the ABCG2 gene polymorphism and a higher chance of drug-resistant epilepsy in children. This finding may have important implications for understanding the role of ABCG2 gene polymorphism in children with drug-resistant epilepsy.